Integrative Model Defense Indonesian Hybrid in Face Dynamics ASEAN Conflict - Suhirwan Suhirwan; Mia Kusmiati (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
Purpose – This article aim For explore idea integrative regarding defense strategy Indonesian hybrid with combine approach conventional, asymmetric, and multidimensional in face complexity conflict in the ASEAN region. Design/ methodology / approach – Research This use systematic literature review (SLR) method on work Suhirwan and Wahyudin (2023), and literature international related defense, regional security, and warfare asymmetrical. This article analyzed 25 sources covering​ books, journals national reputable, and publications international in 2022–2025 period. Findings – The study shows that ASEAN's defense strategy is not can Again only depend on strength conventional, but need framework integrative that includes element diplomacy defense, defense cyber, and the role of actor Civil Defense Model Proposed hybrid​ in article This offer framework adaptive for Indonesia to anticipate threat conventional and non- conventional at a time.Implications practical – This article emphasize that Indonesia needs developing Cyber Forces Independent, strengthening diplomacy defense, as well as build Work The same cross ministries and institutions as part from system defense layered national.​ Originality / Value – Novelty article This lies in the formulation of the Integrative Model Defense Synergistic hybrid​ aspect military regular, defense cyber, counter-terrorism, and diplomacy defense to in One framework strategic. This model give contribution conceptual new for studies defense in ASEAN as well as relevance practical for maker Indonesian policy.